Rancang Bangun Hand Sanitizer Otomatis Berbasis Mikrokontroler yang Dilengkapi dengan Sensor Ultrasonik dan Sensor MLX90614 - Budiana Budiana; Sumantri Kurniawan Risandriya; Hasnira Hasnira; Nanta Fakih Prebianto; Ivan Carlos Hasangapon Panjaitan (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Negeri Batam, 2023)
The outbreak of COVID-19 pandemic has forced society to implement the Clean and Healthy Lifestyle, the one which is washing hands. Hand Sanitizer is an alternative product that could be used to clean hands, besides soap, from pathogenic microorganisms due to physical contact that we did throughout the day. However, it’s necessary to upgrade the working system from manual to automatic, so it would minimalize physical contact during the use. For example is by using Sensor Ultrasonic and IR Temperature Sensor MLX90614. These sensors which are connected to pump, will make an electric and automatic working system of Hand Sanitizer. As the methods, literature study and observation from previous researches/products would be the reference for the design and working system on this research. Eventually, it will help to reduce the spreading of coronavirus in society maximally.